2010
DOI: 10.1128/aac.01584-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Comparison of the Pharmacodynamic Targets for Echinocandin Drugs against Candida Species

Abstract: Previous pharmacodynamic studies using in vivo candidiasis models have demonstrated that the 24-h area under the concentration-time curve (AUC)/MIC is a good descriptor of the echinocandin exposure-response relationship. Further studies investigating the 24-h AUC/MIC target for a stasis endpoint identified free-drug 24-h AUC/MIC against Candida albicans and were similar for two echinocandins, anidulafungin and micafungin. The current studies expand investigation of a third echinocandin (caspofungin) and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
167
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(190 citation statements)
references
References 57 publications
18
167
3
2
Order By: Relevance
“…In agreement with other studies (Andes et al, 2010;FernĂĄndez-Silva et al, 2014;Gil-Alonso et al, 2015;Lepak et al, 2012;Pfaller et al, 2011;Spreghini et al, 2012;SzilĂĄgyi et al, 2012), caspofungin showed excellent in vitro activity against WT clinical isolates as well as against the ATCC 90030 type strain. However, in RPMI 1640, caspofungin killing activity decreased at 16-32 mg l 21 when compared with the killing at 0.25-1 mg l 21 (Table 3).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In agreement with other studies (Andes et al, 2010;FernĂĄndez-Silva et al, 2014;Gil-Alonso et al, 2015;Lepak et al, 2012;Pfaller et al, 2011;Spreghini et al, 2012;SzilĂĄgyi et al, 2012), caspofungin showed excellent in vitro activity against WT clinical isolates as well as against the ATCC 90030 type strain. However, in RPMI 1640, caspofungin killing activity decreased at 16-32 mg l 21 when compared with the killing at 0.25-1 mg l 21 (Table 3).…”
Section: Discussionsupporting
confidence: 80%
“…to allow the fungi to establish tissue infection (BerĂ©nyi et al, 2014;Földi et al, 2012b;KovĂĄcs et al, 2014a, Spreghini et al, 2012Wiederhold et al, 2007). This dosing strategy was based on previous pharmacokinetic studies (Andes et al, 2010;Cornely et al, 2011;Flattery et al, 2011;Migoya et al, 2011;Stone et al, 2002), on previous results from our study group (BerĂ©nyi et al, 2014;Földi et al, 2012b;KovĂĄcs et al, 2014a) and on the findings of Howard et al (2011) At the beginning of therapy (day 1), the fungal kidney burden was determined after dissection of four untreated mice for each isolate (day 1 control burden) (BerĂ©nyi et al, 2014). On day 6 p.i., all mice were sacrificed; both kidneys were removed, weighed and homogenized aseptically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Killing 23 rates (k values) in time-kill and PAFE experiments 24 were determined for each strain and concentration. In 25 time-kill experiments, colony count decreases were 26 isolate-and concentration-dependent at 0.25, 1,4,8,27 16 and 32 mg/L in RPMI-1640, but concentration-28 independent at 1,4,8,16 …”
Section: U N C O R R E C T E D P R O O F U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…99 For time-kill assays (continuous 24-h caspofungin 100 exposure), test solutions were not centrifuged or 101 washed. We used 0.25, 1,4,8,16 and 32 mg/L 102 caspofungin. In case of isolate DPL20, we used 4, 8, 103 16 and 32 mg/L caspofungin.…”
mentioning
confidence: 99%